A Comparative Randomized Controlled Trial Study: The Effects of Court-Type Traditional Thai Massage plus Meditation versus Court-Type Traditional Thai Massage Only on Reducing Pain among the Patients with Myofascial Pain Syndrome - Srikaew, Nunthiya; Pawa, Kammal Kumar; Kietinun, Somboon; Sriyakul, Kusuma; Pattaraarchachai, Junya (Trends in Sciences, 2022)
This study aimed to compare the effectiveness of Court-type traditional Thai massage (CTTM) with Meditation versus CTTM without meditation in decreasing pain stiffness and degree of cervical range of motion (CROM) on participants with myofascial pain syndrome (MPS) on the upper trapezius. The single-blind randomized controlled trial was conducted at Thammasat University Hospital comprising of 64 participants which equally divided into 2 groups. The treatment group received CTTM for 30 min plus meditation and the control group received only CTTM for 30 min each subject received the treatment twice a week for 4 weeks. Assessment of effectiveness was performed by comparing Visual analog scale (VAS), pressure pain threshold (PPT) and CROM were assessed at week 0 (baseline), week 1 - 4 (intervention) and week 6 (follow-up). The VAS and PPT pain score had shown significant differences in both the CTTM plus meditation and CTTM only groups (p < 0.05), whereas the CROM involving flexion, extension, left lateral flexion, and right lateral flexion increased significantly in the CTTM plus meditation but not in CTTM only groups at all assessment time points (p > 0.05). Moreover, all of the measurement were not significant between two groups. These findings showed that both CTTM paired with meditation and CTTM without meditation could alleviate MPS, as evidenced by improvements in VAS, PPT and CROM. Taken together, this research could provide an alternative for people who desire to improve their health by combining CTTM and meditation. HIGHLIGHTS This research insists that Court-type traditional Thai massage plus meditation using neural pathways that make the brain less sensitive to pain Court-type traditional Thai massage combined with meditation has the positive effect pressure pain threshold and cervical range of motion Court-type traditional Thai massage plus meditation may be involved three factors; neurological factors, physiological factors, and mechanical factors to be responsible for reducing pain levels, increasing in pressure pain threshold and improving cervical range of motion